Estimation of white grub damage (Coleoptera : Scarabaeoidea) in cork oak (Quercus suber L.) regeneration parcels of the Mamora forest (Morocco) and search for biological control using sex pheromones. - Ghaioule, Driss; Lumaret, Jean-Pierre; Rochat, Didier; Maatouf, Noureddine; Niogret, Jerome (ANNALES DE LA SOCIETE ENTOMOLOGIQUE DE FRANCE, 2007)
During the last decades, the cork oak restoration in the Mamora forest (Morocco) was faced with massive root attacks of seedling plantations by white grubs (Coleoptera: Scarabaeoidea). In most cases, the success of the restoration reached only 12%. Sphodroxia maroccana Ley (Melolonthidae) can be considered as the main pest in the restoration parcels. Some traits of the biology of this species are specified, despite shortcomings in the knowledge of the precise period of male emergence with regard to females, the longevity of adults and the sex-ratio. Summer drought, a season without white grub activity, is another main cause of mortality of young plantations. During the first year after plantation in experimental parcels, the cumulated mortality due to these two factors ranged between 41 and 68% according to the blocks in the parcels. The mortality associated with S. maroccana larvae ranged between 24 and 43%, with a distribution of infestation depending on density of young plants. Solid phase micro-extraction used to sample volatiles from the headspace of S. maroccana females allowed to isolate resorcinol (1,3-benzenediol) as presumed female sex pheromone. The role of this molecule has to be demonstrated.
The following values have no corresponding Zotero field: pub-location: 45 RUE BUFFON, 75005 PARIS, FRANCE publisher: SOC ENTOMOLOGIQUE FRANCE
Keywords: 1-3-benzenediol; biological control; Cork oak; damage; Morocco; pheromone; resorcinol; Restoration; Scarabaeoidea; white grubs

Estimation of white grub damage (Coleoptera : Scarabaeoidea) in cork oak (Quercus suber L.) regeneration parcels of the Mamora forest (Morocco) and search for biological control using sex pheromones. - Ghaioule, Driss; Lumaret, Jean-Pierre; Rochat, Didier; Maatouf, Noureddine; Niogret, Jerome (ANNALES DE LA SOCIETE ENTOMOLOGIQUE DE FRANCE, 2007)
During the last decades, the cork oak restoration in the Mamora forest (Morocco) was faced with massive root attacks of seedling plantations by white grubs (Coleoptera: Scarabaeoidea). In most cases, the success of the restoration reached only 12%. Sphodroxia maroccana Ley (Melolonthidae) can be considered as the main pest in the restoration parcels. Some traits of the biology of this species are specified, despite shortcomings in the knowledge of the precise period of male emergence with regard to females, the longevity of adults and the sex-ratio. Summer drought, a season without white grub activity, is another main cause of mortality of young plantations. During the first year after plantation in experimental parcels, the cumulated mortality due to these two factors ranged between 41 and 68% according to the blocks in the parcels. The mortality associated with S. maroccana larvae ranged between 24 and 43%, with a distribution of infestation depending on density of young plants. Solid phase micro-extraction used to sample volatiles from the headspace of S. maroccana females allowed to isolate resorcinol (1,3-benzenediol) as presumed female sex pheromone. The role of this molecule has to be demonstrated.
Keywords: 1-3-benzenediol; biological control; Cork oak; damage; Morocco; pheromone; resorcinol; Restoration; Scarabaeoidea; white grubs

UV-band and acid rain effects on beach ( Fagus sylvatica L.) and holm oak ( Quercus ilex L.) leaves - Paoletti, E (Chemosphere, 1998)
Beech (Fagus sylvatica L.) and holm oak (Quercus ilex L) leaves were subjected to simulated acid rain and UV-B radiation for 10 days. The almost glabrous beech leaves revealed a greater predisposition to developing macroscopic necrotic lesions than the pubescent holm oak leaves. This response is due primarily to their different morpho-anatomical structure, rather than to a difference in the synthesis of UV-B absorbing pigments (flavonoids); the response was also accompanied by microscopically observable alterations (collapse of epidermal cells, fusion of surface wax structures, structural damage to the stomata) and by the reduction of stomatal conductance
Keywords: acid rain; beech; damage; Holm oak; leaves; necrosis; stomatal conductance (voyant); uv-b radiation

New type of damage to Quercus ilex: pollen germination and hydration ability - Bellani, Lorenza M.; Paoletti, E. (European Journal of Forest Pathology, 1992)
Pollen grains collected from trees of Quercus ilex L. belonging to different classes of new type damage were analyzed. Five parameters were taken into account: viability, germinability, tube lengthening, grain volume of the dehydrated state and after rehydration. Damage to mother plants clearly influences the above mentioned parameters, causing a reduction in pollen grain viability, germinability, and in the ability of the grains to rehydrate.
Keywords: damage; germination (voyant); pollen; pollution; viability

New types of damage to forest trees typical of the Mediterranean region - Clauser, F; GELLINI, R; Bussotti, F; Cenni, E; Bottacci, A (European Journal of Forest Pathology, 1989)
Since 1984 a new type of damage to the typical tree species growing in the mediterranean area has been observed. The pathological picture includes the typical features of “Waldsterben”. The new symptoms occurring in Pinus pinea, P. pinaster, P. halepensis and Quercus ilex are described.
Keywords: crown damage; damage; decline (voyant); foliage reduction

New types of damage to forest trees typical of the Mediterranean region - Clauser, F.; GELLINI, R.; Bussotti, F.; Cenni, E.; Bottacci, A. (European Journal of Forest Pathology, 1989)
Since 1984 a new type of damage to the typical tree species growing in the mediterranean area has been observed. The pathological picture includes the typical features of “Waldsterben”. The new symptoms occurring in Pinus pinea, P. pinaster, P. halepensis and Quercus ilex are described.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: crown damage; damage; decline (voyant); foliage reduction